Functional interplay among thiol-based redox signaling, metabolism, and ferroptosis unveiled by a genetic variant of TP53 - Leu, Julia I-Ju; Murphy, Maureen E.; George, Donna L. (Proceedings of the National Academy of Sciences - PNAS, 2020)
The p53 tumor suppressor protein is a transcription factor and master stress response mediator, and it is subject to reduction-oxidation (redox)-dependent regulation. The P47S variant of TP53, which exists primarily in African-descent populations, associates with an elevated abundance of low molecular weight (LMW) thiols, including glutathione (GSH) and coenzyme A (CoA). Here we show that S47 and P47 cells exhibit distinct metabolic profiles, controlled by their different redox states and expression of Activating Transcription Factor-4 (ATF4). We find that S47 cells exhibit decreased catabolic glycolysis but increased use of the pentose phosphate pathway (PPP), and an enhanced abundance of the antioxidant, NADPH. We identify ATF4 as differentially expressed in P47 and S47 cells and show that ATF4 can reverse the redox status and rescue metabolism of S47 cells, as well as increase sensitivity to ferroptosis. This adaptive metabolic switch is rapid, reversible, and accompanied by thiol-mediated changes in the structures and activities of key glycolytic signaling pathway proteins, including GAPDH and G6PD. The results presented here unveil the important functional interplay among pathways regulating thiol-redox status, metabolic adaptation, and cellular responses to oxidative stress.